PERAN STAKEHOLDERS DALAM PENGELOLAN EKOWISATA MANGROVE TAPAK, KOTA SEMARANG - Dea Friska Krisyania; Sri Suwitri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The management of Mangrove Tapak Ecotourism in Semarang City faces various challenges. Therefore, stakeholders play an important role in the management of Mangrove Tapak Ecotourism. This study aims to analyze the roles of stakeholders in the management of Mangrove Tapak Ecotourism, Semarang City, as well as to identify and analyze the supporting and inhibiting factors affecting stakeholders’ roles in its management. This research employs a descriptive qualitative approach. Data were collected through interviews, observation, and documentation studies. The results indicate that stakeholders have implemented various strategies in the management of Mangrove Tapak Ecotourism, Semarang City, including the optimization of sustainable coastal resource and environmental utilization, preservation of coastal resource and environmental functions, consideration of regional conditions and potentials as well as local wisdom, and the development of community participation, empowerment, and partnerships. The supporting factors for stakeholders’ roles include conservation policy support, rehabilitation programs and infrastructure, assistance, promotion, as well as coordination and supervision among relevant parties. Meanwhile, the inhibiting factors include limitations in authority and funding of local governments, suboptimal regulations and policy understanding, limited human resources, and the absence of clear mechanisms for cooperation and structured management. An important finding of this study is that policy creators play a minor role in the management of Mangrove Tapak Ecotourism, Semarang City. This is due to policies having limited impact and the managers’ understanding of policies being merely normative in nature.